Untreated dental caries in children with cerebral palsy in the Brazilian context - MARCELA APARECIDA FERREIRA DE CAMARGO (IAPD and Blackwell, 2008)
Cerebral palsy (CP) is an ‘umbrella term’ covering a group of nonprogressive, but often changing motor disorders that occur during early stages of life due to damage to the brain 1 . This syndrome may be congenital or acquired after birth, and its early symptoms usually manifest during the perinatal period. Although CP differs from person to person and may change over time, it often includes difficulties with fine motor tasks, involuntary movements, imbalance and walking inability. Moderately severe or severe CP was estimated to affect from 1.5 to 2.5 per 1000 live births 2 in Brazil. An increase of incidence in Brazil followed an improved survival of children with low birthweight